The Role of Modern Management Accounting Systems in Enhancing The Quality of Accounting Information And Its Reflection on The Administrative Decision-Making Process.: Survey of The Opinions of a Sample of Stakeholders in a Group of Industrial Companies In Sulaimaniyah Province/ Iraq - Hama Amin, Othman Abdulkadir; Mustafa, Wshiar Omar (The Scientific Journal of Cihan University– Sulaimaniya, 2022)
The research represents a step towards the application of modern management accounting systems, which are currently of interest to many countries and companies, in order to improve the level of quality of the information produced from it, and will therefore support administrative decisions taken upon that information. The main aim of the research is to clarify the effect of the application of modern management accounting systems (Target Costing, Value Chain) on improving qualitative characteristics of information, and the reflection of that improvement in the quality of accounting information on the use of that information to support the process of administrative decision-making in industrial companies in Sulaymaniyah Governorate / Iraq. The research was based on the questionnaire form as a field study tool, and the study was applied to a sample of industrial companies in the Sulaymaniyah Governorate that numbered (18) companies. Out of the (180) forms that were distributed to the sampled individuals (160) forms were returned, with a percentage (94%) of the returned forms being valid for analysis. The survey data were analyzed through a program Social Sciences Statistical Package (SSPS). The results of the study show that there is a positive statistically significant relationship between the application and use of modern management accounting systems (TC, VC) and the level of quality of information supporting the administrative decision-making process in industrial companies in Sulaymaniyah Governorate/ Iraq.